Ability to Swim (Not Morphology or Environment) Explains Interspecific Differences in Crinoid Arm Regrowth - Stevenson, Angela; Ó Corcora, Tadhg C.; Harley, Christopher D. G.; Baumiller, Tomasz K. (Frontiers in Marine Science, 2022)
Regrowth of body parts occurs in almost every phylum of the animal kingdom, but variation in this process across environmental, morphological, and behavioral gradients remains poorly understood. We examined regeneration patterns in feather stars – a group known for a wide range of morphologies and behaviors and up to a forty-fold difference in arm regeneration rates – and found that the variation in arm regeneration rates is best explained by swimming ability, not temperature, food supply, morphology (total number of arms and number of regenerating arms), or degree of injury. However, there were significant interactive effects of morphology on rates of regeneration of the main effect (swimming ability). Notably, swimmers grew up to three-fold faster than non-swimmers. The temperate feather star Florometra seratissima regenerated faster under warmer scenarios, but its rates fell within that of the tropical species suggesting temperature can account for intraspecific but not interspecific differences. We urge comparative molecular investigations of crinoid regeneration to identify the mechanisms responsible for the observed interspecific differences, and potentially address gaps in stem cell research.